Foreign experience of the state support of small and medium business. (Journal of Economic Research & Business Administration, 2016)
In this article foreign experience of the state support of small and medium business is analysed. For more expanded studying of experience of the state support of small business in industrialized countries, it is considered system of the state support in some states of Europe, North America. From experience of the state support of small business abroad it is possible to draw a conclusion that the enterprises of small and medium business play a key role in economic development of the state, at the same time their share averages about 60% of total number of the enterprises. The main methods of support are: improvement of the tax law, creation of the special government institutions supervising small business and special funds for support of small and medium business, the help in receiving the credits, creating favorable conditions of external environment, etc.
Keywords: state; state support; small and medium business; small business; state help.